Saccadic Eye Movements and Attentional Control in Alzheimer's Disease. (19th May 2017) - Noiret, Nicolas; Carvalho, Nicolas; Laurent, Éric; Chopard, Gilles; Binetruy, Mickaël; Nicolier, Magali; Monnin, Julie; Magnin, Eloi; Vandel, Pierre
Abstract: Objective: Several studies have demonstrated saccadic eye movement (SEM) abnormalities in Alzheimer's disease (AD) when patients performed prosaccade (PS) and antisaccade (AS) tasks. Some studies have also showed that SEM abnormalities were correlated with dementia rating tests such as the Mini Mental State Evaluation (MMSE). Therefore, it has been suggested that SEMs could provide useful information for diagnosis. However, little is known about predictive saccades (PreS)—saccades triggered before or very quickly after stimuli appearance—and their relationships with cognition in AD. Here, we aimed to examine the relationships between our usual dementia screening tests and SEM parameters in PS, AS, and also PreS task. Method: We compared SEMs in 20 patients suffering from AD and in 35 healthy older adults (OA) in PS, AS, and PreS task. All participants also completed a neuropsychological evaluation. Results: We showed that AD patients had higher latency and latency variability regardless the tasks, and also higher AS cost, in comparison with OA. Moreover, AD patients made more uncorrected AS and took more time-to-correct incorrect AS. In PreS task, AD patients showed higher gain and gain variability than OA when they made anticipated saccades. Close relationships were found between the majority of SEM variables in PS, AS, and PreS tasks and dementia screening tests, especially the MMSE and episodic memory measures. Conclusion: Our findings, in agreement with previous studies, demonstrated that AD affects several SEM parameters. SEM abnormalities may reflect selective and executive-attention impairments in AD.